PRESERVASI KANDUNGAN NUTRISI DALAM PENGOLAHAN PAKAN IKAN BUDIDAYA - Haetami, Kiki; Surahman, Mohammad Badai Putra (Program Studi Budidaya Perairan, Fakultas Pertanian, Universitas Sriwijaya, 2025)
Feed rich in nutrients such as protein, essential fatty acids, vitamins, and minerals plays a central role in successful aquaculture. However, feed processing processes, including extrusion, drying, and encapsulation, often involve extreme conditions such as high temperatures and pressures that can damage sensitive nutrients. The purpose of this literature review is to explore various preservation techniques in aquaculture feed processing to minimize nutrient damage, including temperature control, water content reduction, addition of preservative agents, and modification of chemical composition in an effort to produce feed with good nutritional quality. The method used in compiling this review is the systematic review method. By combining the latest insights from various studies, this review provides strategic guidance for the development of fish feed that is not only efficient and nutritionally stable, but also environmentally friendly. The implications of this innovation are expected to improve the sustainability of aquaculture operations and support responsible fisheries resource management. Based on the results of the study, methods such as drying, fermentation, microencapsulation, and vitamin addition have the potential to increase nutrition in feed and have a good impact on farmed fish.